PROGRESSIVE READING OF CHILD CUSTODY RIGHTS IN INDONESIA: A GENDER JUSTICE PERSPECTIVE ON MARRIAGE LAW - Adi Nur Rohman; Elfirda Ade Putri (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2022)
Disputes over child custody often occur after a divorce. Although the regulation on child custody has been regulated in the Marriage Law and Compilation of Islamic Law (KHI), it is allegedly not responsive enough to gender justice that gives child custody to one party based on the particular type genitals. So this triggers gender inequality and injustice. This article analyses the problem of establishing child custody descriptively analytically with a gender approach as a tool of analysis. This article concludes that the laws and regulations in Indonesia regarding the determination of child custody are still classified as gender-biased and have not been responsive enough to the issue of gender justice. Reciprocal interpretation model (qira'ah mubadalah), as a new approach in understanding the text, if applied in following the rules can be interpreted with the perspective of distinction between men and women who place women and men as human subjects that are whole and equal. Thus, both mothers and fathers alike have the same opportunities in child custody as long as they have qualified abilities in terms of childcare.